1967
DOI: 10.1084/jem.126.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Control of Antibody Synthesis

Abstract: In the system studied, antigenic competition between two haptenic determinants was found to be of the same extent whether the haptens were on the same or on separate carrier molecules. Suppression of antibody formation to one determinant by administration of passive antibody partially eliminated the depressive effects of antigenic competition when the two haptens were located on separate carrier molecules but had no effect on antibody production to the second hapten when the two determinants were present on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(25 citation statements)
references
References 14 publications
(14 reference statements)
2
23
0
Order By: Relevance
“…Fc dependence was implicated by the finding that IgG-mediated suppression in many cases was nonepitope-specific (11, 12, 14 -16), i.e., that IgG specific for one epitope suppresses the response to other epitopes on the Ag. In contrast, epitope-specific suppression has also been observed (17,18). In a novel approach to study the Fc dependence of suppression, we recently showed that IgG can suppress the response to SRBC in mice lacking Fc␥RIIB (Fc␥RIIB Ϫ/Ϫ ), Fc␥RI and III (owing to the lack of the common ␥-chain (FcR␥), Fc␥RI, II, and III (Fc␥RIIB Ϫ/Ϫ ϫ FcR␥ Ϫ/Ϫ double knockouts) or the neonatal FcR, FcRn (owing to the lack of ␤ 2 -microglobulin, which constitutes part of the receptor).…”
mentioning
confidence: 84%
“…Fc dependence was implicated by the finding that IgG-mediated suppression in many cases was nonepitope-specific (11, 12, 14 -16), i.e., that IgG specific for one epitope suppresses the response to other epitopes on the Ag. In contrast, epitope-specific suppression has also been observed (17,18). In a novel approach to study the Fc dependence of suppression, we recently showed that IgG can suppress the response to SRBC in mice lacking Fc␥RIIB (Fc␥RIIB Ϫ/Ϫ ), Fc␥RI and III (owing to the lack of the common ␥-chain (FcR␥), Fc␥RI, II, and III (Fc␥RIIB Ϫ/Ϫ ϫ FcR␥ Ϫ/Ϫ double knockouts) or the neonatal FcR, FcRn (owing to the lack of ␤ 2 -microglobulin, which constitutes part of the receptor).…”
mentioning
confidence: 84%
“…This type of mechanism has been proposed by a number of workers in several experimental systems based on the ability of antiserum directed against certain determinants on a molecule or cell to specifically suppress the response to those determinants without affecting the response to other determinants on the same molecule or cell (29)(30)(31). The ability of T-cells to escape suppression may be explained in such a mechanism by their competing more efficiently than B-cells with the suppressing antiserum for the antigenic determinants or perhaps by their being directed against different determinants than the B-cells.…”
Section: Resultsmentioning
confidence: 99%
“…The potential to modulate an immune response by systemic immunization with antigen bound by antibody has been recognized for some time (11,26,33,36,47,54,68,75,78,79). More recent work has begun to elucidate some of the underlying molecular mechanisms by which antibody may alter an immune response.…”
Section: Discussionmentioning
confidence: 99%